Macroeconomics - McConnell Steve (MC Graw Hill, 2004)
The Student Edition provides a wealth of free resources for students. The Instructor Edition gives instructors password-protected information such as the Instructors Manual, PowerPoints, and Overhead Transparencies. New with the Sixteenth Edition, we also provide a fully integrated pedagogical package for students and instructors: DiscoverEcon with Paul Solman Videos. Students can review key concepts, work with interactive graphs, link out to the Solman Videos on a DVD, complete exercises and multiple choice quizzes, and submit their results to the instructor in the e-submission capacityall with the same text specific system